Going Wild at Oxford - Perry, Charles (Petits Propos Culinaires, 2024)
We do not systematically report on the annual Oxford Symposia on Food History, but from time to time we ask for permission to reproduce something which a symposiast has written for the press, just to keep PPC readers generally in the picture about what goes on at these events. On this occasion we reproduce a report by Charles Perry for the Los Angeles Times. Charles, already well known to PPC readers would be among the most heavily decorated veterans of the Symposia if these were run on military lines. The number of times he has attended and the number of papers he has contributed must constitute some sort of record. Incidentally, the box on the next page tells you how, at long last, it is possible to track down all the 15 years of Symposium papers, by contributor or by subject.